Relationship of Self-Control with Intensity of Tiktok Social Media Use in Universitas Negeri Makassar Studens - Puspita P, RR Atika; Tetteng, Basti; Ismail, Ismalandari (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
. Intensity of tiktok social media use means that how often individuals access so as to produce a behavior or response. One factor that can affect intensity is self-control. The study was conducted to determine the relationship between self-control and the intensity of tiktok social media use in Universitas Negeri Makassar students. This research uses a quantitative approach with person correlation product moment technique. The respondents of study were 381 students of Universitas Negeri Makassar obtained by random sampling.  The results showed that there was a negative relationship between self-control and the intensity of tiktok social media use in Makassar State University students. This is evidenced by a pearson correlation coefficient of -0,311 and the significance value of 0,000 (0,000 0,05), so it can be concluded that the hypothesis is accepted. The implication in the research is that understanding is related to the need for students to have self-control so that they can use their time better and for other useful things.